Growth and Characterization of GaP/GaPAs Nanowire Heterostructures with Controllable Composition. Issue 11 (25th August 2019) - Bolshakov, Alexey D.; Fedorov, Vladimir V.; Sibirev, Nikolai V.; Fetisova, Marina V.; Moiseev, Eduard I.; Kryzhanovskaya, Natalia V.; Koval, Olga Yu.; Ubyivovk, Evgeniy V.; Mozharov, Alexey M.; Cirlin, George E.; Mukhin, Ivan S.
Abstract : Growth and properties of the self‐catalyzed heterostructured GaP nanowires (NWs) with GaP1 − x As x insertions in the form of nanodiscs (NDs) grown by means of molecular‐beam epitaxy on Si (111) substrate are studied. To obtain the NDs with the different composition and optoelectronic properties, the ratio of As and P fluxes is varied. Structural properties of the synthesized heterostructures are characterized by means of transmission electron microscopy. Energy dispersive X‐ray spectroscopy is used to study chemical composition of the NDs. The maximum achieved fraction x in the NDs is nearly 60%. Sublinear dependence of As concentration in the ND on the As/P flux ratio is observed and theoretical description for the observed phenomenon is provided. The proposed model can be used to estimate the predicted As/P ratio for the synthesis of GaPAs NDs as well as NWs of the required composition. Microphotoluminescence (μPL) studies demonstrate the appearance of broadband PL signal in the spectral range between 600 and 700 nm, corresponding to the NDs with different compositions. Spectra intensity modulation is found due to longitudinal Fabry–Pérot‐type resonances in the individual NWs. Abstract : GaP nanowires (NWs) with GaP1 − x As x insertions grown on Si (111) are studied. Sublinear dependence of As concentration in the insertion on the As/P flux ratio is demonstrated and justified theoretically. Microphotoluminescence study shows broadband photoluminescence (PL) signal in the range between 600 and 700 nm. Spectra intensity modulation is found due to longitudinal Fabry–Pérot‐type resonances in the individual NWs.